Myctophid Fish (Family Myctophidae) Are Central Consumers in the Food Web of the Scotia Sea (Southern Ocean) - Saunders, Ryan A.; Hill, Simeon L.; Tarling, Geraint A.; Murphy, Eugene J. (Frontiers in Marine Science, 2019)
Myctophid fish are the most abundant and diverse mesopelagic fishes in the Southern Ocean. They are a conduit of energy between primary consumers and higher marine predators, and between the upper surface layers and the mesopelagic depths. However, there remain major uncertainties about their ecology, particularly regarding their role in Southern Ocean food webs, which are often regarded as dominated by Antarctic krill in waters south of the Antarctic Polar Front. Limited data on the feeding ecology of myctophids has made it difficult to assess the importance of myctophids as consumers of krill and how they fit in the traditional view of a krill-dominated system (diatom-krill-higher predator). We provide a new assessment of the role of myctophids in Southern Ocean food webs using information from recent trophodynamic studies of myctophids conducted in the Scotia Sea, one of the most productive regions of the Southern Ocean and a region that sustains both major populations of higher predators (sea birds, seals, whales) and important commercial fisheries (krill, toothfish and mackerel icefish). Collectively, these data show that myctophids have a central role in Southern Ocean food webs as both predators and prey. Large myctophid species are prevalent consumers of krill throughout their distributional range and in different seasons in the Scotia Sea. Moreover, best estimates of both myctophid and higher predator consumption of krill to date indicate that large myctophids are the greatest predators of krill in this region, consuming almost as much krill as all other vertebrate predators of krill. Nevertheless, there are several smaller myctophid species that do not eat krill, instead consuming copepods and other small euphausiids. Myctophids therefore link primary producers to higher predators through both krill-dependent and krill-independent trophic pathways, emphasizing their importance in regional food webs. Consequently, myctophid-based trophic pathways are unlikely to be exempt from the direct consequences of a redistribution and/or reduction in krill population biomass. The extent to which myctophids can maintain food web stability and sustain higher predator populations during periods of prolonged reductions in krill abundance is considered further.